Biomedical and Health Informatics Education – the IMIA Years - Mantas, J. (Yearbook of medical informatics, 2016)
Summary Objective: This paper presents the development of medical informatics education during the years from the establishment of the International Medical Informatics Association (IMIA) until today. Method: A search in the literature was performed using search engines and appropriate keywords as well as a manual selection of papers. The search covered English language papers and was limited to search on papers title and abstract only. Results: The aggregated papers were analyzed on the basis of the subject area, origin, time span, and curriculum development, and conclusions were drawn. Conclusions: From the results, it is evident that IMIA has played a major role in comparing and integrating the Biomedical and Health Informatics educational efforts across the different levels of education and the regional distribution of educators and institutions. A large selection of references is presented facilitating future work on the field of education in biomedical and health informatics.